LATAR BELAKANG SOSIAL EKONOMI MASYARAKAT NAGARI SUNGAI SARIAK KECAMATAN VII KOTO KABUPATEN PADANG PARIAMAN - Erita, M.Pd, Dr. Yeni; Setriani, Loli (Jurnal Spasial, 2018)
Without the interaction made by humans it is certain that humans will not be able to live in this world. Social interaction is the main requirement of social activities. Social interaction is a dynamic social relationship involving relations between individuals, between groups, as well as between individuals and groups. With the social interaction done by the people of Sungai Sariak can fulfill everyday kebuhan, where the main livelihood of society of Sungai Sariak is farming and trading. The purpose of this research is to know and analyze the socio-economic background of the Sariak River nagari community, using descriptive method. Judging from the result obtained that seen from (1) formal education of society in Nagari Sungai Sariak sub district VII Koto Regency of Padang Pariaman, show: (3,85%) never school, (30,75%) finished primary school (23,08 %) finished junior high school, (42%) graduated from high school, and (0%) finished college. (2) The community interacted with the children of the nephew at Nagari Sungai Sariak subdistrict VII Koto Padang Pariaman District showed: (61,53%) always, (15,38%) often, (23,07%) occasionally and (0% ) never. (3) The income of the community in Nagari Sungai Sariak shows: (23.07%) income <Rp 1,000,000, (38,46%) earning Rp 1,000,000 - Rp 2,000,000, and (38,46%) earning> Rp 2,000,000. (4) People's entrepreneur in Nagari Sungai Sariak showed: (38,46%) farming, (46,15%) trading, (0%) PNS, (11,54%) self-employed and (3,85%) as unemployment .  Keywords: Education, Interaction, Income, and livelihood.